2020
DOI: 10.1186/s12877-020-01700-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in community-dwelling older adults using the updated EWGSOP2 definition according to kidney function and albuminuria

Abstract: Background Loss of muscle mass and function may be more pronounced in older adults with chronic kidney disease (CKD) and with albuminuria. Thus, we investigated the prevalence of sarcopenia among community-dwelling older adults according to kidney function and grade of albuminuria. We also explored differences in the prevalence of sarcopenia according to three different equations for the estimation of glomerular filtration rate (eGFR). Methods A cross-sectional analysis of 1420 community-dwelling older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
2
26
0
4
Order By: Relevance
“…Sarcopenia prevalence (probable/confirmed/severe sarcopenia) was 18.1% ( n = 81) at baseline, when using the revised EWGSOP2 definition. The prevalence of sarcopenia in our population‐based sample of middle‐aged and older men is similar to the findings of Moreno‐Gonzalez et al 31 . In their study with 1420 European community‐dwelling older adults (>75 years), 22.1% of men could be classified into one of the sarcopenia categories of EWGSOP2 31 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Sarcopenia prevalence (probable/confirmed/severe sarcopenia) was 18.1% ( n = 81) at baseline, when using the revised EWGSOP2 definition. The prevalence of sarcopenia in our population‐based sample of middle‐aged and older men is similar to the findings of Moreno‐Gonzalez et al 31 . In their study with 1420 European community‐dwelling older adults (>75 years), 22.1% of men could be classified into one of the sarcopenia categories of EWGSOP2 31 .…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of sarcopenia in our population‐based sample of middle‐aged and older men is similar to the findings of Moreno‐Gonzalez et al . 31 In their study with 1420 European community‐dwelling older adults (>75 years), 22.1% of men could be classified into one of the sarcopenia categories of EWGSOP2. 31 Sarcopenia prevalence and incidence in EMAS, according to other definitions [International Working Group on Sarcopenia (IWGS), EWGSOP1, Baumgartner], have been described elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 145) analyzed the nationwide prospective cohort of CKD in Korea and reported that normal body mass index with central obesity has increased risk of coronary artery calcification, and adipose tissue volume has a significant correlation with VC. 146) 147) In addition, the prevalence of low muscle mass is increased as CKD is more advanced 148) and sarcopenia in hemodialysis patients shows an independent relationship with VC. 149) These results suggest that pathogenesis of obesity, sarcopenia and VC may involve some shared mechanism, and inflammation is potential common pathway of them.…”
Section: Clinical Implication Of Vascular Calcification In Chronic Kidney Diseasementioning
confidence: 99%
“…Chronic kidney disease (CKD) is often called a model of ‘accelerated ageing’; therefore, it is likely that the loss of lean mass, reduced skeletal muscle strength, and low physical performance (all components of sarcopenia) are in the same direction as patient‐centred outcomes of ageing such as mobility limitations, disability, and mortality as in the general population 22 . Although some criteria have been developed to define sarcopenia, 4 the feasibility of using such criteria in CKD patients has not yet been clarified yet 23 . The type of test used to detect sarcopenia may influence the diagnosis of sarcopenia in CKD patients 24 .…”
Section: Introductionmentioning
confidence: 99%